An Empirical Study of Association between Working Capital Management and Performance: Evidence from Tehran Stock Exchange - Ahmadpour, Ahmad; ., Keramatollah Heydari Rostami (Journal of Social and Development Sciences, 2012)
Present study is aimed at determining the effects of working capital management on the performance of firms. In this research, we have selected a sample of 112 Iranian firms listed on Tehran Stock Exchange for a period of 10 years from 2000–2009, we have studied the effect of different variables of working capital management including the Average collection period, Inventory turnover in days, Average payment period and Cash conversion cycle on the financial performance of Iranian firms. Debt ratio, Current ratio, size of the firm (measured in terms of natural logarithm of sales), financial assets to total assets ratio and Stock Exchange Index have been used as control variables, Correlation, and regression analysis (Pooled least square and general least square with cross section weight models) are used for analysis. The results show that there is a strong negative relationship between variables of the working capital management and profitability of the firm.